Design, synthesis, antimicrobial activity and anticancer screening of some new 1,3-thiazolidin-4-ones derivatives - Shehab, Wesam Saber; Mouneir, Samar Mohamed (European Journal of Chemistry, 2015)
A series of new thiazolidin-4-ones have been synthesized by the reaction of 3-acetylindole with thiourea to yield 2-amino-arylthiazole (1) which, reacted with 2-chloroacetyl chloride to produce 2-chloroacetamido-4-arylthiazoles (2). The later was treated with potassium thiocyanate to afford the related 2-amino-3-(4-arylthiazol-2-yl) thiazolidin-4-ones (3). Condensation of compounds 1 and 3 with different aromatic aldehydes give Schiff’s bases (4a-c) and (5a-c) reaction of compound 5a-c with thioglycollic acids furnishes the target thiazolidin-4-one molecules (6a-c). Further, condensation of compound 6a with benzaldehyde affords benzylidenethiazolo derivative (7) which on refluxing with malononitrile, acetylacetone afforded thiazolopyridine derivatives (8,9). Structure elucidation of the products has been accomplished on the basis of elemental analysis, IR, 1H NMR data. Compound 3exhibited the most potent antibacterial and anticancer activity.